2021
DOI: 10.1177/13591053211067102
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between COVID-19-induced death thoughts and depression during a national lockdown

Abstract: Evidence suggests that the COVID-19 pandemic has increased rates of depression worldwide. Many factors have been identified to relate to this increase depression, but according to Terror Management Theory, the heightened awareness of death during the pandemic has the potential to increase depression for those with low self-esteem. This hypothesis was examined in a U.K. sample during the first national lockdown where depression, self-esteem and death-thought accessibility (DTA) were measured, and a COVID Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…Additionally, a large proportion of the population experienced the loss of family members or beloved ones among the over 150,000 deaths due to COVID-19 in Germany ( 72 ). Nevertheless, recent studies indicate that an increased salience of death due to the COVID-19 pandemic would also be associated with an increase in the level of depressive symptoms, which was not the case in the present study ( 73 75 ). Additionally, Russia's invasion of Ukraine, which started in February 2022, the recent energy crisis, economic changes, rising inflation rates, climate change and related worry in youths and adolescents ( 76 78 ) could, to some extent, contribute to an explanation of this specific increase in only suicidal ideation, but further research is needed.…”
Section: Discussioncontrasting
confidence: 85%
“…Additionally, a large proportion of the population experienced the loss of family members or beloved ones among the over 150,000 deaths due to COVID-19 in Germany ( 72 ). Nevertheless, recent studies indicate that an increased salience of death due to the COVID-19 pandemic would also be associated with an increase in the level of depressive symptoms, which was not the case in the present study ( 73 75 ). Additionally, Russia's invasion of Ukraine, which started in February 2022, the recent energy crisis, economic changes, rising inflation rates, climate change and related worry in youths and adolescents ( 76 78 ) could, to some extent, contribute to an explanation of this specific increase in only suicidal ideation, but further research is needed.…”
Section: Discussioncontrasting
confidence: 85%
“…People's sources of meaning in life help to achieve psychological adaptation (Chen et al, 2022 ). Further research findings suggest that heightened existential questions may be a neglected factor in increasing depression during the pandemic (Fairlamb, 2022 ). Our findings of cognitive changes can be challenging for the atheist state of the Czech Republic.…”
Section: Discussionmentioning
confidence: 99%
“…During the first stage of the COVID-19 pandemic, the prevalence of depression and anxiety significantly increased worldwide (Xiong et al, 2020 ; Pieh et al, 2021 ; Fairlamb, 2022 ; Yu et al, 2022 ). The United Nations has issued a warning regarding the emergence of mental health crisis related to COVID-19 (Xiong et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are significant impacts of the COVID-19 pandemic and lockdown measures on psychological wellbeing including anxiety and depression, [ 22 , 23 ] and psychological wellbeing is known to influence patients' quality of life and perceptions of their pain and function [ 24 26 ]. However, despite this, our study has shown no overall differences in ODI scores between patients during lockdown and those taken from patients before lockdown.…”
Section: Discussionmentioning
confidence: 99%